HIGH -RESOLUTION CT PULMONARY CHANGES IN PATIENTS WITH CYSTIC FIBROSIS USING BHALLA SCORE SYSTEM CORRELATED WITH CLINICAL PARAMETERS - Dimitrijevikj, Kristina; Mitreska, Nadica; Vasilevska-Nikodinovska, Violeta (Journal of Morphological Sciences; Vol 6 No 3 (2023): JMS, 2023)
Cystic fibrosis (CF), caused by a mutation in the cystic fibrosis transmembrane conductance regulator (CFTR) gene, is an inherited, chronic, progressive, and fatal disease.It mainly involves the lungs and pancreas, but also the upper airways, liver, intestine, and reproductive organs. The aim of our study is to evaluate one of the most used scoring systems, the Bhalla scoring system, in the detection of lung impairment in patients with cystic fibrosis. A total of 32 patients diagnosed with CF came to our University clinic of pulmonology and allergology-Skopje to perform HRCT for the first time and to detect the degree of the disease. Clinical data, age at application, deep throat and sputum cultures were obtained from medical records Moj Termin. High-resolution computed tomography (HRCT) was performed on a 128-slice PHILIPS INCISIVE CT scanner, using 1 mm slices and a high spatial resolution image reconstruction algorithm using Bhaala score system.  A total of 66% of patients have mild severity of bronchiectasis, 53% of all have mild peribronchial thickening. 41% of all have from 1 to 5 extent of the bronchiectasis and 53% of all have from 1 to 5 extend of mucus plugs as a dominant HRCT findings. Sputum was positive in 44 % of patients.  High resolution computed tomography (HRCT) is well-established and is the current â€œgold standardâ€ method for monitoring lung anatomical changes in patients with CF. Bhalla HRCT scoring system is useful for pulmonary evaluation of children with CF. Key words: cystic fibrosis, HRCT, Bhaala score.